Inteligência: representações do cenário internacional e seus reflexos no Brasil (1935-1941) - Costa, Alexandre Andrade da [UNESP] (2014)
The purpose of this research is to study Inteligência, monthly magazine of world opinion, founded by Mario Graciotti in 1935, in São Paulo. This review constitutes a relevant source for research, since it brought about the texts and caricatures organized and translated by intellectuals who joined the Society of Political Studies (SEP), founded in 1932. Intended be analyzed from your pages, that way the publishers represented the different political and ideological contexts that clashed with the purpose of acting, modify or justify domestic political positions without losing sight that the published texts resulted from choices that can not be separated from the worldview of its creators. Regarding the methodology, it is to grasp the magazine as a source and object of study